TEST RESPONSE OF ETAWAH CROSSBREED GOAT MILK THAT WAS STORED AT ROOM TEMPERATURE - J.,N.P, Nugroho; Mariani, N.P.; Okarini, I.A. (Jurnal Peternakan Tropika; Vol 7 No 1 (2019): Vol. 7 Isssues 1 (2019); January - April 2019, 2019)
Milk has high nutrition, this causes milk to be a medium that is very favored by microorganisms for their growth and development. Damage that occurs in milk results in a decrease of it quality that can be known by test of it. This study aims to determine the fat content, alcohol test, LAB and flavor of milk during storage of room temperature. Milk samples were obtained from Etawah Crossbreed (PE) dairy goat farms in Sepang Village, Busung Biu District, Buleleng Regency. This research was conducted for 1 month from 29 June - 2 August 2018. The design used was a Completely Randomized Design (CRD), with 3 storage treatments at room temperature namely P 0 (0 hour of storage), P 4 (4 hours of storage) and P 6 ( 6 hours of storage) repeated 4 times, so the samples examined were 12 samples. The variables observed in this study were alcohol test, fat content, amount of LAB and flavor. The data obtained were analyzed with variance, if there were significant differences (P<0.05) then the analysis continued with Duncan's multiple range test. The results showed that the alcohol test at P 0 and P 4 were negative results, while on P 6 was a positive result. Fat content of P 4 (86.04%) and P 6 (49.35%) and P 4 BAL (44.5%) increased significantly (P<0.05) compared to P 0 . P4 taste (17.14%) and P 6 (35.71%) significantly decreased (P<0.05) compared to P 0 with the longer storage time. Based on the results of the study it can be concluded that the goat milk stored for 4 hours at room temperature was the best treatment in maintaining milk freshness in terms of alcohol test, fat content, total LAB and flavor preferences. Keywords: Goat milk, storage, alcohol test, LAB, fat content, flavor